Profile of an occupation – management assistant in e-commerce - Schambeck, Arne [Verfasser] (My University, 2024)
Over the past few years, e-commerce has led to the creation of new task areas, processes and business models with their own ways of working and sequences which were not covered by the established commercial occupations. This made it necessary to introduce a new occupation to provide training for tasks in the area of e-commerce. This profile presents the tasks, development opportunities and figures for this new occupation which entered into force in 2018. (BIBB-Doku)
Keywords: S 6.4.1 Kaufleute; 370; Kaufmännische Ausbildung; Kaufmann im E-Commerce; Tätigkeitsmerkmal; Berufsbeschreibung; Fortbildungsabschluss